Adoribatella, Ferolocella, Joelia and Ophidiotrichus (Acari, Oribatida, Oribatellidae) of North America - Behan-Pelletier, Valerie M. (Zootaxa, 2013)
In North America, species diversity in the oribatid family Oribatellidae is primarily in the genus Oribatella Banks, but the genera Adoribatella Woolley, Ferolocella Grabowski, Joelia Oudemans and Ophidiotrichus Grandjean are also represented. I provide detailed diagnoses for these genera and the previously described species, Adoribatella punctata Woolley, known from Colorado and Oregon, USA, and Alberta, Canada, Ferolocella tessalata Berlese known from Missouri, Virginia, West Virginia, Georgia, Wisconsin, Ohio, Alabama, Arkansas and Texas, USA, and Ophidiotrichus exastus Woolley, known from North Carolina, Alabama, Missouri, Tennessee and Georgia, USA. I describe Joelia appalachia sp. nov., based on adult specimens, from West Virginia. A key is given to distinguish adults of these genera from those of Oribatella. Character states shared by adults of Oribatellidae are discussed, the synonymy of Gendzella Kuliev with Ferolocella is rejected, and arguments are presented for movement of Adoribatella from Oribatellidae to the Ceratozetoidea.